Interventions used by health care professionals to transition preterm infants and neonates from enteral feeds to full-oral feeds: A Scoping review - Rabbipal, Yajna (Department of Health and Rehabilitation Sciences, 2022)
Background: Preterm infants and neonates may present with dysphagia due to immaturity or the presence of medical conditions. Enteral feeds are used to ensure optimal nutrition is achieved while the neonates are developing appropriate oral feeding skills. Varied interventions may be used to transition neonates to full oral feeds as oral feeding is often a prerequisite for discharge from hospital. Aims: The main aim of this study was to summarize, interpret and analyse the literature on the different interventions used for the transition to full oral feeds in preterm infants and neonates to identify research gaps and to inform clinical practice on the best intervention options. A secondary aim was to validate the findings of the scoping review for the South African context. Methods: A scoping review was conducted. Relevant studies were identified by searching six databases, Google and Google scholar. Inclusion criteria included studies written in English, peer reviewed and published between 1998–2018, that described the interventions used to transition preterm infants and neonates to full oral feeds. Data were extracted from the articles using a data charting form and analysed descriptively and thematically. The findings were shared with health care professionals who work with premature infants and neonates who then participated in a semi-structured interview to provide feedback relevant to the South African context. Results: Forty-seven articles were included. Six broad intervention categories were identified: oral-motor, oral-sensory, other senses, timing, cue-based and utensils. Non-nutritive sucking (NNS) interventions were reported most frequently across single and combined interventions. Outcome measures reported included: time taken to full oral feeds, earlier hospital discharge, long-term feeding outcomes, weight and sucking proficiency. Improved outcomes were associated with NNS and NNS with oral stimulation. Nine health care professionals were interviewed. They confirmed using a number of the interventions, with NNS reported the most. Health care professionals also provided insight into the challenges of implementing some interventions due to limited resources and staffing in the South African context. Conclusions: There are a range of interventions reported in the literature and many of them are used in South Africa. Positive outcomes such as earlier transition to full oral feeds; earlier hospital discharge; improved weight gain and improved sucking proficiency have been reported with NNS and combined NNS and Oral Stimulation interventions, however further studies are needed.